2018
DOI: 10.1186/s13750-018-0136-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the impacts of agroforestry on agricultural productivity, ecosystem services, and human well-being in high-income countries: a systematic map protocol

Abstract: Background: Agroforestry bridges the gap that often separates agriculture and forestry by building integrated systems that address both environmental and socioeconomic objectives. Agroforestry can improve the resiliency of agricultural systems and mitigate the impacts of climate change. Existing research suggests that integrating trees on farms can prevent environmental degradation, improve agricultural productivity, increase carbon sequestration, generate cleaner water, and support healthy soil and healthy ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(75 citation statements)
references
References 54 publications
2
69
0
4
Order By: Relevance
“…Indeed, every crop has speci c environmental requirements in order to achieve optimum yield, which in this case is the minimum light requirement. However, several studies have shown that crops can grow well and productive in the agroforestry system, as long as some basic requirements met [39]. For instance, cacao can achieve the productivity of 50% and higher when planted together with 100 shade trees per hectare in a spatially organized manner [40].…”
Section: Monetary Value From Different Land Use Crop Pattern and Comentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, every crop has speci c environmental requirements in order to achieve optimum yield, which in this case is the minimum light requirement. However, several studies have shown that crops can grow well and productive in the agroforestry system, as long as some basic requirements met [39]. For instance, cacao can achieve the productivity of 50% and higher when planted together with 100 shade trees per hectare in a spatially organized manner [40].…”
Section: Monetary Value From Different Land Use Crop Pattern and Comentioning
confidence: 99%
“…There are numerous proven advantages from agroforestry which did not directly calculate as income, instead, it offers services that can be calculated as a nancial loss when such services did not exist anymore. Several crucial ecosystem services identi ed from agroforestry systems, i.e., help to mitigate the effects of climate change, increase the water and air quality, improve the soil structure and nutrient cycling, increase carbon sequestration, increase the water in ltration from surface runoff, control of pest and diseases, and helps to conserve related biodiversity [39,42,43]. Such knowledge was not readily accessible for the local farmers in BW.…”
Section: Monetary Value From Different Land Use Crop Pattern and Comentioning
confidence: 99%
“…International organizations and governments have been investing in agroforestry research and projects in lower-middle-income countries since the 1960s and 1970s [5,21,22], exploring the interactions between agroforestry and ecosystem oriented services in the world, as well as specifically in the Asia-Pacific region [18]. For instance, Chang et al [19] analyzed bird biodiversity in a coffee agroforestry system in India, Yang et al [23] described the impact of riparian buffers on biomass in China, and Tiwari et al [24] calculated the ecosystem services of maize from hillside agroforestry systems in Nepal, but each of these studies focused on only one type of agroforestry.…”
Section: Introductionmentioning
confidence: 99%
“…One of the solutions for synthesizing the information, when there is disparate evidence, is a systematic map, providing a robust method to identify and present research evidence extracted from peer-reviewed papers and grey literature [22,[32][33][34]. The rigorous methodology describes the characteristics and trends of research on a broad scale, and, in part, fills the knowledge gaps by bringing together repeatable and quantitative evidence [33,34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation